The Impact of Education Policies in Asia on Access and Quality of Education in Developing Countries - Grace Tan Mei Ling (International Journal of Advanced Research, 2025)
This study examines the impact of education policies in Asia on improving access to and the quality of education in developing countries. Using a mixed-methods approach and interval-based regression analysis, the research investigates policy outcomes across five Asian nations—Indonesia, Vietnam, Bangladesh, Pakistan, and the Philippines—from 2015 to 2020. Key policies analyzed include curriculum reform, teacher training, infrastructure investment, and tuition subsidies. Results indicate that while most countries have made notable progress in increasing access to education, improvements in quality have been uneven. Vietnam and Indonesia show the most significant gains due to sustained investment and strong policy implementation frameworks. In contrast, Pakistan and Bangladesh lag due to limited capacity and inconsistent reforms. The findings underscore the importance of aligning education policies with local socio-economic contexts, investing in teacher development, and adopting digital innovations. Moreover, the study finds that policy impacts tend to diminish over time without continued innovation and adaptive leadership. These insights suggest that educational success in developing countries depends not only on access-oriented reforms but also on sustained efforts to improve instructional quality and institutional resilience. This research contributes to policy discourse by offering practical implications for governments, development agencies, and education stakeholders seeking to improve equity and outcomes across Asia’s developing regions.